Effectiveness of maggot extractions and secretion (E/S) of Lucilia sericata in reducing wound surface in experimental scalding burn injury - Zahra Sadat Amiri; Kamran Akbarzadeh; Masoumeh Douraghi; Khosrou M Abdi; Abbas Aghaei Afshar; jasem ghaffari; Razieh shabani Kordshouli; Morteza Akbari; Javad Rafinejad (Nusantara Bioscience, 2021)
Abstract. Amiri ZS, Akbarzadeh K, Douraghi M, Abdi KM, Afshar AA, Ghaffari J, Kordshouli RS, Akbari M, Rafinejad J. 2021. Effectiveness of maggot extractions and secretion (E/S) of Lucilia sericata in reducing wound surface in an experimental scalding burn injury. Nusantara Bioscience 13: 11-15. Lucilia sericata larvae have been successfully used as medicinal larvae for wound healing. This study was performed to evaluate the therapeutic effects of the primary ointment made from excretory-secretory substances of L.sericata larvae on experimental burn wounds on rabbits under laboratory conditions. Extraction of ES from the third stage of L.sericata larvae and antibiogram testing was done. Four rabbits were randomly divided into four groups; three standard third-grade burn wounds were created on the back of each rabbit for intervention groups (B, D) of wounds were used respectively from the original ointment made from ES and ES without accompanying material. Nitrofurazone ointment was used for the positive (C) and placebo ointment was used for the negative (A). On the 21st day, all scars of wounds in groups B and D were separated and the wound was free of infectious tissue, whereas in groups A and C that the scars were clinging to the base. The level of the ulcer was significantly lower in the E/S intervention group and the infectious tissue was not observed during the treatment of group B and D wounds. Methicillin-resistant Staphylococcus aureus (MRSA) did not show resistance to excretory-secretory substances of L. sericata larvae. The debridement and recovery process was faster in the ES-treated group and the initial ointment than in the control group. The results showed that maggot extractions and secretion (E/S) of L. sericata in reducing wound healing is appropriate for treatment.